Health and production effects of killed vaccines against Mannheimia haemolytica, bovine viral diarrhoea virus and bovine herpesvirus 1, in locally backgrounded feedlot cattle. Issue 1 (15th July 2020) - Cusack, PMV; Bergman, EL; Hay, KE; Morton, JM
Abstract : Objectives: This study evaluates the effects of respiratory vaccines on health and growth rates in cattle placed in local backgrounding facilities then feedlots. Methods: A total of 7011 cattle entering backgrounding facilities contiguous with six feedlots in Australia were allocated to eight respiratory vaccine categories, including an untreated control category. The vaccines, against Mannheimia haemolytica, bovine viral diarrhoea virus and bovine herpesvirus 1, were administered in various combinations at backgrounding facility entry and subsequent feedlot entry. Cattle were held in the backgrounding facilities for a minimum of 28 days. Results: During their feedlot phase, 3.7% of study animals were detected with bovine respiratory disease (BRD). BRD sub hazard was lowest in cattle vaccinated with Bovilis MH + infectious bovine rhinotracheitis® (sub hazards ratio: 0.47; 95% confidence interval: 0.27–0.83; P = 0.010), and point estimates for other vaccine combinations did not differ (P > 0.10) from controls. Six of the respiratory vaccine combinations decreased growth rate during backgrounding relative to untreated controls (P ≤ 0.003). Overall, the feedlot growth rate was not significantly affected by the vaccine category (overall Wald P = 0.191). Conclusions: Use of these respiratory vaccines in cattle held for at least 28 days in backgrounding facilities contiguous with their feedlots before feedlot entry reduces growth rate during the backgrounding period and does not result in large beneficial effects on either BRD risk or average daily live weight gain during the feedlot phase.